Fibrinolytic and coagulative activities of Yersinia pestis - Korhonen, Timo K.; Haiko, Johanna; Laakkonen, Liisa; Järvinen, Hanna M.; Westerlund-Wikström, Benita (Frontiers in Cellular and Infection Microbiology, 2013)
The outer membrane protease Pla belongs to the omptin protease family spread by horizontal gene transfer into Gram-negative bacteria that infect animals or plants. Pla has adapted to support the life style of the plague bacterium Yersinia pestis. Pla has a β-barrel fold with 10 membrane-spanning β strands and five surface loops, and the barrel surface contains bound lipopolysaccharide (LPS) that is critical for the conformation and the activity of Pla. The biological activity of Pla is influenced by the structure of the surface loops around the active site groove and by temperature-induced LPS modifications. Several of the putative virulence-related functions documented for Pla in vitro address control of the human hemostatic system, i.e., coagulation and fibrinolysis. Pla activates human plasminogen to the serine protease plasmin and activates the physiological plasminogen activator urokinase. Pla also inactivates the protease inhibitors alpha-2-antiplasmin and plasminogen activator inhibitor 1 (PAI-1) and prevents the activation of thrombin-activatable fibrinolysis inhibitor (TAFI). These functions enhance uncontrolled fibrinolysis which is thought to improve Y. pestis dissemination and survival in the mammalian host, and lowered fibrin(ogen) deposition has indeed been observed in mice infected with Pla-positive Y. pestis. However, Pla also inactivates an anticoagulant, the tissue factor (TF) pathway inhibitor, which should increase fibrin formation and clotting. Thus, Pla and Y. pestis have complex interactions with the hemostatic system. Y. pestis modifies its LPS upon transfer to the mammalian host and we hypothesize that the contrasting biological activities of Pla in coagulation and fibrinolysis are influenced by LPS changes during infection.